DESIGN OF CONTAINER TERMINAL JETTY STRUCTURE BASED ON BRITISH STANDARD IN PANTOLOAN TERMINAL, TELUK PALU PORT, PALU, CENTRAL SULAWESI - Reynaldi, Alvin
The earthquake and tsunami of Palu Bay in late September 2018 was one of the biggest natural disaster events in 2019 that shook Indonesia. This event caused a significant loss of life and damage to essential facilities supporting the economy. One of the public facilities greatly affected by this disaster was the harbour located in Palu Bay, including Pantoloan Harbour, Donggala Harbour, and Wani Harbour, which played a crucial role in driving the economy of Central Sulawesi Province. This Final Project discusses the planning of a container terminal at Pantoloan Terminal, Palu Bay Harbour, Central Sulawesi. The dock's design references British Standards, Indonesian National Standards, and the American Society of Civil Engineers. The discussions in this Final Project cover the processing of secondary data, structural modeling of the dock using SAP2000, design of reinforcement for dock structural elements, and analysis of soil bearing capacity. The UCR target for this dock structure design ranges from 0.7 to 1, and the deflection values are kept below the permissible deflection. Reaction forces will be used to analyze soil bearing capacity, and internal forces will be used for the design of reinforcement for dock structural elements. The resulting dimensions of the designed dock are a length of 250 meters and a width of 40 meters. The elevation of the dock is +4.5 meters above Lowest Water Spring (LWS), and the water depth is -11 meters from LWS. Dock structural elements consist of slabs, beams, pile caps, and piles. Two types of beams are used: longitudinal transverse beams and crane beams. Three types of pile caps are used corresponding to the types of piles. Piles include fender piles, crane beam piles, and regular piles. The outcome of this Final Project is a planned design comprising dock structural dimensions, berthing and mooring facilities for ships, dimensions of structural elements, reinforcement design for structural elements, and soil bearing capacity analysis.